Advantages and limitations of virtual online consultations in a NHS acute trust: the VOCAL mixed-methods study - Sara Shaw; Joseph Wherton; Shanti Vijayaraghavan; Joanne Morris; Satya Bhattacharya; Philippa Hanson; Desirée Campbell-Richards; Seendy Ramoutar; Anna Collard; Isabel Hodkinson; Trisha Greenhalgh (National Institute for Health Research, 2018)
Background: There is much enthusiasm from clinicians, industry and the government to utilise digital technologies and introduce alternatives to face-to-face consultations. Objective(s): To define good practice and inform digital technology implementation in relation to remote consultations via Skype™ (Microsoft Corporation, Redmond, WA, USA) and similar technologies. Design: Multilevel mixed-methods study of remote video consultations (micro level) embedded in an organisational case study (meso level), taking account of the national context and wider influences (macro level). Setting: Three contrasting clinical settings (Diabetes, Antenatal Diabetes and Cancer Surgery) in a NHS acute trust. Data collection and analysis: Macro level - interviews with 12 national-level stakeholders combined with document analysis. Meso level - longitudinal organisational ethnography comprising over 300 hours of observations, 24 staff interviews and analysis of 16 documents. Micro level - 30 video-recorded remote consultations; 17 matched audio-recorded face-to-face consultations. Interview and ethnographic data were analysed thematically and theorised using strong structuration theory. Consultations were transcribed verbatim and analysed using the Roter interaction analysis system (RIAS), producing descriptive statistics on different kinds of talk and interaction. Results: Policy-makers viewed remote video consultations as a way of delivering health care efficiently in the context of rising rates of chronic illness and growing demand for services. However, the reality of establishing such services in a busy and financially stretched NHS acute trust proved to be far more complex and expensive than anticipated. Embedding new models of care took much time and many resources, and required multiple workarounds. Considerable ongoing effort was needed to adapt and align structures, processes and people within clinics and across the organisation. For practical and safety reasons, virtual consultations were not appropriate for every patient or every consultation. By the end of this study, between 2% and 20% of all consultations were being undertaken remotely in participating clinics. Technical challenges in setting up such consultations were typically minor, but potentially prohibitive. When clinical, technical and practical preconditions were met, virtual consultations appeared to be safe and were popular with both patients and staff. Compared with face-to-face consultations, virtual consultations were very slightly shorter, patients did slightly more talking and both parties sometimes needed to make explicit things that typically remained implicit in a traditional encounter. Virtual consultations appeared to work better when the clinician and the patient knew and trusted each other. Some clinicians used Skype adaptively to support ad hoc clinician-initiated and spontaneous patient-initiated encounters. Other clinicians chose not to use the new service model at all. Conclusions: Virtual consultations appear to be safe, effective and convenient for patients who are preselected by their clinicians as 'suitable', but such patients represent a small fraction of clinic workloads. There are complex challenges to embedding virtual consultation services within routine practice in the NHS. Roll-out (across the organisation) and scale-up (to other organisations) are likely to require considerable support. Limitations: The focus on a single NHS organisation raises questions about the transferability of findings, especially quantitative data on likely uptake rates. Future research: Further studies on the micro-analysis of virtual consultations and on the spread and scale-up of virtual consulting services are planned. Funding: The National Institute for Health Research Health Services and Delivery Research programme.